2015
DOI: 10.1016/j.physleta.2014.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Controlling the energy gap of graphene by Fermi velocity engineering

Abstract: The electronic structure of a single-layer graphene with a periodic Fermi velocity modulation is investigated by using an effective Dirac-like Hamiltonian. In a gapless graphene or in a graphene with a constant energy gap the modulation of the Fermi velocity, as expected, only changes the dispersion between energy and moment, turning the minibands narrower or less narrow than in the usual graphene depending on how the Fermi velocity is modulated and the energy gap remains the same. However, with a modulated en… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 35 publications
1
22
0
2
Order By: Relevance
“…which is square integrable for a state with quantum number m as long as the velocity barrier grows at large distances more rapidly than v F (r → ∞) ∼ r −2m . These wavefunctions (27) and (28) display the chiral property of total suppression of the electronic probability density on one of the the two sublattices, dependent on the sign of the angular momentum m.…”
Section: Zero-energy States In Radial Velocity Barriersmentioning
confidence: 99%
“…which is square integrable for a state with quantum number m as long as the velocity barrier grows at large distances more rapidly than v F (r → ∞) ∼ r −2m . These wavefunctions (27) and (28) display the chiral property of total suppression of the electronic probability density on one of the the two sublattices, dependent on the sign of the angular momentum m.…”
Section: Zero-energy States In Radial Velocity Barriersmentioning
confidence: 99%
“…In the last years, various studies have revealed that the electronic and transport properties of graphene can be controlled by a Fermi velocity engineering [43,44]. For instance, it was obtained that a Fermi velocity modulation in graphene can control the energy gap [45] and also induce an indirect energy gap in monolayer [46] and bilayer [47] graphene. The Fermi velocity can also be used to create electrons guides in graphene [48,49], to control the Fano factor [50] and to tune the electrons transmittance from 0 to 1 [51], which means that it can turn on/off the transport in graphene.…”
Section: Introductionmentioning
confidence: 99%
“…A position-dependent Fermi velocity can be obtained by placing metallic planes close to the graphene lattice, which will change the electron concentration in different regions [34,35]. It has been shown, for instance, that a Fermi velocity modulation can be used to control the energy gap of graphene [36], to induce an indirect energy gap in monolayer [37] and bilayer graphene [38], to engineer the electronic structure of graphene [39,40] and to create a waveguide for electrons in graphene [34,35]. Most recently, it was shown that it is possible to tune the transmitivity of electrons in graphene from 0 to 1 with the Fermi velocity, which can be used to turn on/off the electronic transport in graphene [41].…”
Section: Introductionmentioning
confidence: 99%